Macrophomina phaseolina infection and water relations in mungbean genotypes - SATISH LODHA, UDAY BURMAN and (Indian Phytopathology, 2002)
In 1993 Vigna radiata genotypes PDM-86-199 and K851 were planted in a loamy sand soil with a 10.4% (w/w) moisture holding capacity in Jodhpur, Rajasthan, India. Genotype K851 was more susceptible to M. phaseolina infection than PDM-86-199 and it hada bigger drop in shoot water potential following infection.